The Influence of Organizational Culture and Motivation on Employee Engagement of Civil Servants at the Regional Office of the Ministry of Religious Affairs of West Kalimantan - Novrian Ananda Ramadhan; Irfan Mahdi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of organizational culture and work motivation on the employee engagement of Civil Servants (PNS), both partially and simultaneously. The study employs a quantitative approach with an associative design. The population and sample consist of 132 civil servants (total sampling). Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS, supported by instrument validity and reliability tests, classical assumption tests (normality, linearity, and multicollinearity), correlation coefficient (R), coefficient of determination (R²), as well as F-test and t-test at a 0.05 significance level. The results indicate that organizational culture and work motivation simultaneously have a positive and significant effect on employee engagement. Partially, both organizational culture and work motivation also have a positive and significant effect on employee engagement. An R value of 0.660 indicates a strong relationship, while an R² value of 0.436 suggests that 43.6% of the variation in employee engagement is explained by organizational culture and work motivation, whereas the remaining 56.4% is influenced by other factors outside the model. Theoretically, this study strengthens organizational behavior literature by confirming the role of organizational culture and motivation as determinants of employee engagement within the public-sector bureaucratic context. Practically, the findings provide a basis for institutions to reinforce a constructive work culture and manage motivation systematically to improve employee attachment.